Rendimento, valor nutritivo e características fermentativas de silagens de grãos úmidos de cereais de inverno - Biazus, Valdéria (2018)
The South of Brazil is characterized by milk producing properties that have the necessity to use of the available area in an efficient way. Integrated systems of agricultural production (SIPA), among them the agriculture-cattle integration (ILP), which integrates activities with the objective of optimizing the use of the ground, infrastructure and labor, minimizing costs and diluting the risks. Produce moist grains silage of winter cereals, after grazing in autumn and winter, followed by deferral for harvesting grain is a strategy to generate more income in the winter. The ensiling aims to conserve the nutrients of the ensiled material through the anaerobic fermentation, with minimal loss of dry matter and energy. The grain silage may be an option of concentrate supplementation in the management of food of animal production, leading to a significant reduction of the costs of feed. The objective of this work was to evaluate the productivity, nutritional value and the fermentation characteristics of silage of moist grains of winter cereals. The experiments were conducted in the experimental field of Embrapa Trigo in the city of Coxilha (RS) in the years 2016 and 2017. Two production systems were evaluated with four species of winter cereals, blank oats, barley, wheat and triticale. In the first system was simulated the ILP system, in which there was a harvest of green fodder and later wet grain harvest for silage. In the second system has not been carried out cutting, only wet grain harvest that were ensiled. The experimental design was in randomized blocks with four repetitions. The variables evaluated were plant stature, contents and dry matter yield, nutritive value of the forage yield and nutritive value of grain and silage, pH, specific mass and losses in silage. It was observed that the winter cereals have suitable characteristics for the production of silage in the two production systems.